3(x+1)(x+2)-2(3x-4)(x+2)+(x-2)(4x+2)=..
Ajutorr...plss!
Răspunsuri la întrebare
Răspuns de
0
3(x+1)(x+2)-2(3x-4)(x+2)+(x-2)(4x+2)=
=(3x+3)(x+2)-(6x-8)(x+2)+(x-2)(4x+2)=
=(x+2)(3x+3-6x+8)+(x-2)(4x+2)=
=(x+2)(-3x+11)+(x-2)(4x+2)=
=-3x²-6x+11x+22+4x²-8x+2x-4=
=x²-x+18
=(3x+3)(x+2)-(6x-8)(x+2)+(x-2)(4x+2)=
=(x+2)(3x+3-6x+8)+(x-2)(4x+2)=
=(x+2)(-3x+11)+(x-2)(4x+2)=
=-3x²-6x+11x+22+4x²-8x+2x-4=
=x²-x+18
gaby140:
afla nr necunoscut (4×b+5)_6×2=5
Alte întrebări interesante
Geografie,
8 ani în urmă
Geografie,
8 ani în urmă
Limba română,
8 ani în urmă
Matematică,
9 ani în urmă
Engleza,
9 ani în urmă
Matematică,
9 ani în urmă
Matematică,
9 ani în urmă